Immobilization of Cu(II)-Histidine Complex on Al-MCM-41 as Catalyst for Epoxidation of Alkenes - F. Farzaneh (Journal of Sciences, Islamic Republic of Iran)
Cu(II) complex with L-histidine (His) ligand, immobilized within Al-MCM-41, designated as Cu(His)2/Al-MCM-41 was prepared and characterized by powder X-ray diffraction (XRD), nitrogen adsorption desorption, FTIR, UV-Vis and chemical analysis techniques. The surface area and pore volume were found to decrease after immobilization of Cu(II) complex on Al-MCM-41. It was found that Cu(His)2/Al-MCM-41 catalyze the oxidation of some alkenes such as norbornene and trans-stilbene with tert-butylhydroperoxide (TBHP) with high activity and selectivity to the corresponding epoxides. It was concluded that the Al-MCM-41 nanoreactors is a suitable support for immobilization of biomimetic molecules. Particularly significant is that no desorption was observed during the course of reactions.